Antibacterial Activity and Color Evaluation of Natural Color Fabric from Terminalia bellerica Coated with TiO2 - Amalia, Rizka; Pujiastuti, Alfyan; Paramita, Vita; Kusumayanti, Heny (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2023)
As a basic human need, the development of textiles still needs to be studied. At first, the textile dyeing process used natural dyes. However, along with the development of technology with the discovery of synthetic dyes for textiles, the use of natural dyes began to be abandoned. Natural color fabrics have many advantages, while promoting disadvantages, such as the appearance of microorganisms on the fabric. To improve the function of the fabric, the addition of antibacterial agent to the fabric is important. This study aims to investigate the optimum condition for producing natural color fabric from Terminalia Belerica’s peel with the application of TiO2 as an antibacterial agent, using the pad dry cure method. The results of the TiO2 coating process on natural dye fabrics are based on its antimicrobial activity. SEM EDX, color strength, and fabric stiffness were also characterized by its physical properties. The analysis results show that the most optimum condition for the stability of color aging was in the 2nd experiment at a concentration of TiO2 at 1%, without curing and sizing of 75%. For stiffness stability analysis, the optimum result was obtained in the third experiment, namely the concentration of TiO2 at 0.5%, with curing and without sizing of 98%. The most influential effects on the antibacterial test include aging, brightness, and stiffness, namely variable sizing with a negative effect. The results of testing antibacterial activity on natural color fabrics of jolawe fruit peel extract applied with TiO2 show that the assessment process caused the fabric to be easily contaminated by bacteria, where the inhibition zone value was 0 mm. The SEM-EDX test did not show any damage to the fabric, and there were grains or lumps on the fabric fibers due to TiO2 coating.